2021
DOI: 10.3389/fphys.2021.640199
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Energy Contributions and Workloads in Male and Female Badminton Players During Games Versus Repetitive Practices

Abstract: PurposeThe aim of this study was to compare the energy contributions and workloads in men and women during badminton matches versus frequently used multi-ball smash practices.MethodsFourteen badminton players performed one badminton singles game and one session of smashing practice on separate days. The energy contributions were examined in terms of each individual’s three energy systems and substrate oxidation, while workloads included heart rate (HR), Player Load (PL), accelerations, decelerations, changes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The average heart rate of the players in the present study was 151 ± 12 b·min −1 , corresponding to 82 ± 10%HRM. Despite lower average heart rates in our study, similar values of 83%HRM were reported in sub-elite young adult badminton players [ 10 ]. Elite youth competitors had higher average heart rates of 183 b·min −1 and %HRM of 89.8% during the first game and 184 b·min −1 and 90.8%HRM during the second game of simulated match play [ 35 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The average heart rate of the players in the present study was 151 ± 12 b·min −1 , corresponding to 82 ± 10%HRM. Despite lower average heart rates in our study, similar values of 83%HRM were reported in sub-elite young adult badminton players [ 10 ]. Elite youth competitors had higher average heart rates of 183 b·min −1 and %HRM of 89.8% during the first game and 184 b·min −1 and 90.8%HRM during the second game of simulated match play [ 35 ].…”
Section: Discussionsupporting
confidence: 87%
“…For example, in a review by Phomsoupha et al [ 9 ] in 2015, it was stated that between 60–70% of adenosine triphosphate resynthesis was provided by oxidative sources. However, newer quantifications have adjudged this figure to be in excess of 94% [ 10 ]. Accordingly, the applicability of antecedent research to contemporary performance may be limited, and without procuring specific knowledge of the current physiological demands, training regimens are likely outdated and ineffective [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The training of badminton specific tasks, such as on court footwork and other movements, may need to consider the gender-based aerobic and anaerobic capacities in male and female athletes (Y. Fu et al, 2021), fatigue effect on injury risks (Herbaut & Delannoy, 2020;Valldecabres, Richards, et al, 2020), athletic level (or performance) based (Barnamehei et al, 2020;Mei et al, 2017), and physiological load and biomechanical impact (Alder et al, 2019;Yu et al, 2021).…”
Section: Development Of Badminton Sport Trainingmentioning
confidence: 99%
“…Specifically, "Pattern training method" is a control method to organize and grasp the process of sports training according to the requirements of highly representative normative goal model. (Chen, 2014;Y. Fu et al, 2021;Mcguigan et al, 2006).…”
Section: Badminton Footwork Trainingmentioning
confidence: 99%
See 1 more Smart Citation